Comparison of Ultrasonic Device Versus Bipolar Diathermy Tonsillectomy in Children - Sah, Mukesh Kumar; Neupane, Yogesh; Guragain, Rajendra Prasad (Journal of Nepal Health Research Council, 2019)
Background: Intraoperative bleeding and postoperative pain are two commonest concerns for both patient and surgeon in tonsillectomy. This study was aimed to compare intraoperative blood loss and early postoperative pain between ultrasonic device and bipolar diathermy tonsillectomy in children. Methods: Prospective, interventional, single blinded, comparative study was carried out from September 2016 to September 2017 including children up to age 15 years who underwent tonsillectomy either by bipolar diathermy or ultrasonic device. Intraoperative blood loss was recorded using standard sized gauge technique. Post-tonsillectomy pain on first five postoperative days (early postoperative pain) was assessed using Visual analog scale for children older than 5 years and FLACC score for children up to 5 years respectively.Means were compared. Results: 38 children (76 tonsils) were included in the study out of which 31 were boys (62 tonsils) and 7 were girls (14 tonsils). The mean intraoperative blood loss in ultrasonic dissection group was 13.94 ml and 13.91 ml in bipolar diathermy group. This difference was not statistically significant (p=0.974). Post-operative pain on 1st, 2nd, 3rd and 4th days were significantly less (p<0.05) in ultrasonic device group compared to bipolar diathermy group. Post-operative pain was less also on 5th post-operative day in ultrasonic device but was not statistically significant (p=0.172). Conclusions: Tonsillectomy in children using ultrasonic device did not differ from bipolar diathermy tonsillectomy in respect to intraoperative blood loss. However, early postoperative pain was significantly lower in ultrasonic device group. Keywords: Bipolar diathermy; tonsillectomy; ultrasonic device.